CHALLENGE LEARNING FOR TEACHERS IN RURAL GWERU ZIMBABWE - Bhebhe, Gladwin; Mugurani, Matiya (SCAD Independent, 2016)
The study established that rural day secondary school science teachers face a number of challenges, including inadequate teaching and learning materials, students’ negative attitudes towards science, conflicts between students’ home background and school science, and absence of science teachers’ associations. These challenges could have a direct impact on the teaching and learning of science in rural day secondary schools. The opening of rural day secondary schools in Zimbabwe was a great challenge in terms of providing science education to all students because the newly opened secondary schools did not have conventional laboratories and equipment that would facilitate the teaching and learning of science. This study sought to find out the challenges faced by rural day secondary school science teachers in Gweru district of Zimbabwe and propose a way forward. Questionnaires, interviews and observations were used to collect data pertaining to the challenges that were faced by the teachers.